2023
DOI: 10.3390/pathogens12081068
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Spread, Diagnosis, and Control of African Swine Fever in the Philippines

Chia-Hui Hsu,
Rachel Schambow,
Maximino Montenegro
et al.

Abstract: African Swine Fever (ASF) is a highly contagious disease that threatens the swine industry globally. Since its introduction into the Philippines in 2019, ASF has spread extensively in both commercial and backyard farms. Here, using a mix of qualitative and quantitative methods, including conjoint and SWOT analyses, world café discussions, and multivariable regression models, the most important factors that influence the spread, diagnosis, and control of ASF in the Philippines were identified. Research findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In backyard or smallholder settings, certain characteristics are notable in these countries. Firstly, there is a tendency to purchase live pigs of poor quality [ 36 ]. Additionally, the feeding of pigs with swill is a common practice, despite being prohibited or not recommended by the government.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 99%
See 1 more Smart Citation
“…In backyard or smallholder settings, certain characteristics are notable in these countries. Firstly, there is a tendency to purchase live pigs of poor quality [ 36 ]. Additionally, the feeding of pigs with swill is a common practice, despite being prohibited or not recommended by the government.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 99%
“…While the Philippines has attempted to implement a progressive control strategy similar to that employed and improved upon in historical FMD control, the progress has been limited. The challenges encountered in controlling ASF in the country include a shortage of trained manpower, the intricacies of the swine value chain (lack of traceability), and the persistence of high-risk practices in specific farming sectors and live animal trade [36]. In Taiwan and Japan, the primary risk of ASF introduction is associated with border control inspections, as studies indicate ASFV can be detected in pork products brought by travelers [37][38][39][40].…”
Section: December 2019mentioning
confidence: 99%
“…The implementation of Administrative Circular No. 12, Series of 2019 (National Zoning and Movement Plan for the Prevention and Control of African Swine Fever) was among the initial government responses to the ASF outbreak, designating different zones based on ASF risk levels [ 59 ]. The zoning and compartmentalization program of three different regions in the Philippines is based on disease status, protecting unaffected areas while controlling disease in infected areas.…”
Section: Asf Control and Prevention Strategiesmentioning
confidence: 99%
“…Important risk factors in ASF spread, such as infected raw meat, pork products, environmental fomites, vertebrate or invertebrate hosts, contaminated feeds, and wild pigs, should also be monitored and included in the epidemiological model. In a conjoint analysis conducted by Hsu et al, swill or contaminated feed was reported to be the most significant factor influencing ASF spread in the Philippines [ 59 ]. Although wild boar or feral pigs are less likely to be associated with the ASF spread, ASF in wild boar may be under-reported in Asia [ 59 , 61 ].…”
Section: Asf Control and Prevention Strategiesmentioning
confidence: 99%
“…In connection with the handling of FMD in Japan and Indonesia, SWOT analysis was used to look at strengths, weaknesses, opportunities, and threats regarding conditions when the outbreak occurred in Japan in 2010 and in Indonesia in 2022. Similar research using SWOT analysis was also used during the outbreak of African Swine Fever (ASF) in the Philippines by Hsu et al (2023). This research gathered various perspectives on current conditions, diagnosis, and ASF control policies.…”
Section: Introductionmentioning
confidence: 99%